2001
DOI: 10.1097/00007632-200109010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Results From Chemonucleolysis With Chymopapain or Collagenase

Abstract: After 5 years, no deterioration had occurred, as compared with the 1-year follow-up assessment. Chymopapain has proved to be safe, with one minor anaphylactic reaction, and effective even over the long term. Collagenase may need further study and cannot be recommended at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Purified bacterial collagenase, derived from Clostridium histolyticum , has also been used for chemonucleolysis. A prospective randomized study using chymopapain and collagenase showed good and excellent outcomes 5 years after treatment in 72 % of the chymopapain group and in 52 % of the collagenase group [42]. In addition, a prospective randomized trial of 100 consecutive lumbar HD patients was performed to determine whether chemonucleolysis with chymopapain or standard discectomy showed better or improved outcomes.…”
Section: Development Of a Less Invasive Treatment For Hdmentioning
confidence: 99%
“…Purified bacterial collagenase, derived from Clostridium histolyticum , has also been used for chemonucleolysis. A prospective randomized study using chymopapain and collagenase showed good and excellent outcomes 5 years after treatment in 72 % of the chymopapain group and in 52 % of the collagenase group [42]. In addition, a prospective randomized trial of 100 consecutive lumbar HD patients was performed to determine whether chemonucleolysis with chymopapain or standard discectomy showed better or improved outcomes.…”
Section: Development Of a Less Invasive Treatment For Hdmentioning
confidence: 99%
“…46 One further study 61 did not report any global effect, pain intensity or CSOM data. 61 Three studies compared different types of chemonucleolysis [211][212][213] and one study 213 included three intervention arms.The types of chemonucleolysis being compared are listed in Table 31b, but the findings of these studies are not considered any further than this.…”
Section: Summary Of Overall Findings For Epidural/intradiscal Injectimentioning
confidence: 99%
“…47,48,51,56,205 However, these were experienced by only one or two participants within each study (that compared chemonucleolysis with another types of treatment). One study 211 that compared two types of chemonucleolysis (with 5 years' follow-up data) reported slightly higher levels of serious adverse effects. When combining data from both treatment arms (n = 50), 12 participants experienced severe pain and 11 experienced neurological deficit.…”
Section: Analysis Of Adverse Effects For Chemonucleolysismentioning
confidence: 99%
“…Studies had documented the effect of epidural steroids in the symptomatic of disc prolapsed as early as 1952 when hydrocortisone was used by Robecchi and Capra. [14] The rationale for anti-inflammatory treatment with preganglionic steroid infiltration in the relief of the preganglionic inflammation by ensuring recovery of the normal ganglioneural myelin sheath, and hence nerve function at the disease site, [15,16] and is an effective tool for the relief of root pain caused by spondylosis or disk herniation, but the effects appear to be short lived. [17,18] The success rates with epidural steroid injection vary in literature but most studies report a good success rate in short term while the average success rate at 6 months has been 30-49%.…”
Section: Discussionmentioning
confidence: 99%